The Perspective of Integrated Islamic Elementary School (SDIT) Students Regarding the Needs of English Language Teaching Material to Develop Islamic-Based Language Literacy - Amalia, Taranindya Zulhi; Fitriati, Sri Wuli; Mujianto, Januarius; Widiati, Utami (Journal of English Teaching and Learning Issues, 2025)
This research was conducted due to problems that arose in integrated Islamic elementary schools (SDIT) due to a lack of English language teaching materials aligned with the Islamic school orientation. This study innovates by developing English language teaching material models for SDITs. It examines the need for these models from the perspective of SDIT students. Qualitative methods and research and development (R&D) were employed. Data was collected through a questionnaire containing ten close-ended questions and one open-ended question. The results indicate that Integrated Islamic elementary schools (SDIT) need more English language teaching materials, even though they like the current materials. They enjoy singing in English but find reading English stories difficult. Additionally, they mentioned wanting content about Muslim children's daily lives and fun games added to their English language teaching materials. In conclusion, Integrated Islamic elementary schools (SDIT)’s perspectives indicate that the development of English language teaching material models is needed.